2022
DOI: 10.1021/acscentsci.2c00977
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Effective Monoclonal Antibody against Heroin and Its Metabolites Reveals Therapies Have Mistargeted 6-Monoacetylmorphine and Morphine over Heroin

Abstract: The opioid epidemic is a global public health crisis that has failed to abate with current pharmaceutical treatments. Moreover, these FDA-approved drugs possess numerous problems such as adverse side effects, short half-lives, abuse potential, and recidivism after discontinued use. An alternative treatment model for opioid use disorders is immunopharmacotherapy, where antibodies are produced to inhibit illicit substances by sequestering the drug in the periphery. Immunopharmacotherapeutics against heroin have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…34 Thus, several lines of evidence point to the importance of binding 6-AM instead of heroin. A recent study concluded that mAbs binding heroin and not 6-AM are critical for the reduction of heroin analgesia 37 ; however, uncertainties regarding the pharmacokinetics of heroin when given intraperitoneally could challenge this conclusion.…”
Section: Immunotherapeutic Prevention Of the Effects Of Heroinmentioning
confidence: 99%
“…34 Thus, several lines of evidence point to the importance of binding 6-AM instead of heroin. A recent study concluded that mAbs binding heroin and not 6-AM are critical for the reduction of heroin analgesia 37 ; however, uncertainties regarding the pharmacokinetics of heroin when given intraperitoneally could challenge this conclusion.…”
Section: Immunotherapeutic Prevention Of the Effects Of Heroinmentioning
confidence: 99%
“…The colonies that produced active antibodies were then identified and isolated. The complete elimination of murine components resulted in the development of mAbs that were largely less immunogenic and, in many cases, had enhanced pharmacokinetic profiles that slowed their clearance from plasma [62].…”
Section: Immunotherapy In Neuropathies Treatmentmentioning
confidence: 99%
“…This is crucial not only to mitigate the risk of abuse-induced overdose 9 but also to facilitate dosage monitoring. 10 To date, various analytical methodologies have been employed to quantify morphine and its metabolites 11 in diverse biological matrices, including enzyme immunoassay, 12 gas chromatography 13 (GC), liquid chromatography 14 (LC), gas chromatographymass spectrometry 15 (GC-MS), and liquid chromatography-mass spectrometry 16 (LC-MS). Mass spectrometry is widely recognized as the predominant analytical method among these techniques due to its unparalleled detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%